2020
DOI: 10.1177/1545968320948071
|View full text |Cite
|
Sign up to set email alerts
|

Attentional Resource Associated With Visual Feedback on a Postural Dual Task in Parkinson’s Disease

Abstract: Background Restricted attentional resource and central processing in patients with Parkinson’s disease (PD) may reduce the benefit of visual feedback in a dual task. Objectives Using brain event-related potentials (ERPs), this study aims to investigate the neural mechanisms of posture visual feedback and supraposture visual feedback during performing of a posture-motor dual task. Methods Eighteen patients with PD and 18 healthy controls stood on a mobile platform (postural task) and executed a manual force-mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 40 publications
2
1
0
Order By: Relevance
“…Our results were opposite to our expectations and went against, in part, the predictions of our first hypothesis. Individuals with PD increased the COP velocity when they received the VF compared to the OE condition corroborating with previous study that also observed that PD did not use the real-time VF to reduce their sway 31 . There is a two-fold explanation for the increased postural sway in our study: a difficulty in integrating the information provided by the VF 9,32 or a delay in the sensory integration as reported in previous study 13 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results were opposite to our expectations and went against, in part, the predictions of our first hypothesis. Individuals with PD increased the COP velocity when they received the VF compared to the OE condition corroborating with previous study that also observed that PD did not use the real-time VF to reduce their sway 31 . There is a two-fold explanation for the increased postural sway in our study: a difficulty in integrating the information provided by the VF 9,32 or a delay in the sensory integration as reported in previous study 13 .…”
Section: Discussionsupporting
confidence: 90%
“…It is possible to relate this with increased muscle contraction, hypertonicity, or rigidity 37 , due to the task instruction to stay as still as possible, influencing more the peripheral postural control mechanisms 38 . Overall, these findings corroborate with the information that individuals with PD have difficulty to use the additional visual information to improve postural stability 31,33 . Future studies should investigate whether individuals with more advanced PD and with different clinical characteristic (e.g., freezing of gait) have different responses to VF of the COP.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation